Mutational analysis of the Potyviridae transcriptional slippage site utilized for expression of the P3N-PIPO and P1N-PISPO proteins - Olspert, Allan; Carr, John; Firth, Andrew (Oxford University Press, 2019)
The Potyviridae comprise the largest and most important family of RNA plant viruses. An essential overlapping ORF, termed pipo, resides in an internal region of the main polyprotein ORF. Recently, expression of pipo was shown to depend on programmed transcriptional slippage at a conserved GAAAAAA sequence, resulting in the insertion of an extra A into a proportion of viral transcripts, fusing the pipo ORF in frame with the 5 third of the polyprotein ORF. However, the sequence features that mediate slippage have not been characterized. Using a duplicate copy of the pipo slip site region fused into a different genomic location where it can be freely mutated, we investigated the sequence requirements for transcriptional slippage. We find that the leading G is not strictly required, but increased flanking sequence GC content correlates with higher insertion rates. A homopolymeric hexamer is optimal for producing mainly single-nucleotide insertions. We also identify an overabundance of G to A substitutions immediately 3'-adjacent to GAAAAAA in insertion-free transcripts, which we infer to result from a 'to-fro' form of slippage during positive-strand synthesis. Analysis of wild-type and reverse complement sequences suggests that slippage occurs preferentially during synthesis of poly(A) and therefore occurs mainly during positive-strand synthesis.